2022
DOI: 10.3889/oamjms.2022.10904
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Expression of GLUT1 in Renal Cell Carcinoma and its Various Subtypes

Abstract: BACKGROUND: Renal cell carcinoma is one of the most common tumors of the kidney. Glucose transporters, transport glucose, and increased expression of these transporters have been reported in various tumor types. Glucose transporter 1 (GLUT1), the best-known glucose transporter, has an important role at several stages in cancer progression. The overexpression of GLUT1 in the tumor cells indicates an increased proliferation and invasive behavior of the tumor. AIM: This study aims to investigate the expression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
0
0
0
Order By: Relevance
“…In the current study, ccRCC 786-O cells were exposed for 24, 48, 72, and 96 h to several concentrations of BAY-876. The results demonstrated that BAY-876 can reduce 786-O cells in a dose-dependent manner and the IC 50 was 53.56x10 -6 M. As RCC specimens demonstrated a remarkably significant rise in the expression levels of GLUT1 compared with the corresponding normal kidney tissue ( 36 , 37 ), the present finding proves that reducing cell glucose intake by inhibiting GLUT1 through BAY-876 treatment, could represent a new strategy to suppress the growth of ccRCC. Moreover, the present result is consistent with a recent study ( 38 ) showing that BAY-876 has an inhibitory effect against bladder urothelial carcinoma (BLCA) cell lines and tumor inhibition effect in xenograft models.…”
Section: Discussionsupporting
confidence: 55%
“…In the current study, ccRCC 786-O cells were exposed for 24, 48, 72, and 96 h to several concentrations of BAY-876. The results demonstrated that BAY-876 can reduce 786-O cells in a dose-dependent manner and the IC 50 was 53.56x10 -6 M. As RCC specimens demonstrated a remarkably significant rise in the expression levels of GLUT1 compared with the corresponding normal kidney tissue ( 36 , 37 ), the present finding proves that reducing cell glucose intake by inhibiting GLUT1 through BAY-876 treatment, could represent a new strategy to suppress the growth of ccRCC. Moreover, the present result is consistent with a recent study ( 38 ) showing that BAY-876 has an inhibitory effect against bladder urothelial carcinoma (BLCA) cell lines and tumor inhibition effect in xenograft models.…”
Section: Discussionsupporting
confidence: 55%